The future of Building Information Modeling (BIM) software in the construction industry /masjid di Pulau Pangkor, Perak) / Mohamad Zain Hashim and Muriatul Khusmah Musa - Hashim, Mohamad Zain; Musa, Muriatul Khusmah (Unit Penerbitan PKAPP, 2024)
The future of Building Information Modeling (BIM) software in the construction industry is poised for transformative growth, driven by technological advancements and a shift towards more sustainable, efficient, and collaborative construction practices. This comprehensive overview encapsulates the essence of BIM's evolution, its current state, technological impacts, sustainability efforts, collaboration and project management enhancements, the importance of training and education, and future predictions, all aimed at understanding the profound influence BIM will continue to have on the construction industry.